Meningkatkan kompetensi pedagogik guru non-kependidikan dalam penyusunan perencanaan pembelajaran melalui supervisi akademik - Ahmad Basahil (JPPTK: Jurnal Pendidikan Pembelajaran & Penelitian Tindakan, 2021)
Teachers as the spearhead of education and as determinants of success in printing quality human resources are required to have professionalism in carrying out their duties and functions as teaching staff. Teaching or teaching and learning process is basically a process that is arranged in such a way according to certain steps so that its implementation achieves the expected results. Every lesson plan is always related to projections or estimates of what will be done when carrying out teaching. The success of the implementation of learning must begin with careful planning. Therefore, the teacher's ability to make a good lesson plan (RPP) as part of the teaching planning process is absolutely owned by the teacher as a component that supports the implementation of effective teaching and learning activities so that learning objectives can be achieved perfectly. The main purpose of this school action research is to help improve the pedagogical competence of teachers at SDN Malay 2 Banjarmasin who do not have a teacher education background, in preparing learning plans that are in accordance with the competency standards of each lesson so that they can be used as references in the learning process so that participants students are able to achieve the minimum completeness criteria. The type of research used is school action research, consisting of action planning, action implementation, observation, and reflection. The data collection technique uses classroom observation techniques. The results showed that there was an increase in the competence of non-educational teachers in preparing lesson plans.